2. KINERJA PEMERINTAH YANG DIPERTANYAKAN - Widowati, Nina (Faculty of Social and Political Sciences Diponegoro University, 2007)
Half of the 5-year period of the Government under Susilo Bambang Yudhoyono-Yusuf Kalla has been carried out. There are many problems that have to be resolved by the president and his ministers. The performance of the government always becomes public debate. Bureaucracy pathology is a government’s homework that should be accounted for the public. In line with this condition, it needs transparency and accountability of the government in order to bring about the change of bureaucracy behaviour.